Densification, strengthening and toughening in hafnium carbide with the addition of silicon carbonitride. Issue 5 (14th January 2020) - Hao, Wei; Ni, Na; Guo, Yi; Li, Chuanwei; Fan, Xiaohui; Xiao, Weiwei; Zhao, Xiaofeng; Xiao, Ping
Abstract: Hafnium carbide (HfC) possesses low toughness and damage tolerance, which limits its application as high‐temperature structural materials. Here we report a route to fabricate a dense HfC with high toughness by incorporating a two‐component SiCN (silicon carbonitride) sintering aid, which is composed of SiCN and turbostratic carbon in the spark plasma sintering. The addition of the SiCN not only enhances the density (up to ~97%) of the final product,  but more importantly results in an increase in toughness from 4.3 to 8.5 MPa m 1/2 with only a 10% reduction in the flexural strength. The improvement has been attributed to the unique microstructure of the obtained samples, exhibiting several important characteristics: (a) homogeneously dispersed SiCN and C secondary phases in the HfC matrix to control grain size; (b) HfC grains contain different levels of Si, O,  and N to form solid solution; (c) enrichment of free carbon at grain boundaries and triple junctions. Abstract : A two‐component SiCN (silicon carbonitride, SiCN) sintering aid containing SiCN and turbostratic carbon was incorporated into HfC to fabricate a composite microstructure featuring (i) homogeneously dispersed SiCN and C secondary phases in the HfC matrix to control grain size, (ii) formation of solid solution with different levels of Si, O and N, and (iii) enrichment of free carbon at grain boundaries and triple junctions. The unique microstructure results in an ~180 % increase of the toughness measured by both SENB and indentation methods.